Stress and coping among Polish and Slovak athletes during the second stage of the COVID-19 pandemic - Makarowski, R. (Physical Education, Sport and Kinetotherapy Journal, 2020)
The aim of this study was to estimate variability in experienced stress, the use of personal resources (resilience) in coping with stress and the Big Five personality traits among Polish and Slovak athletes. The study used the Perception of Stress Questionnaire to measure the following dimensions: emotional tension, external stress and intrapsychic stress. The Resilience Scale was also used, comprising five subscales: perseverance and determination, openness to new experiences and sense of humour, competences and tolerance of negative emotions, tolerance of failure and treating life as a challenge, optimism and the ability to mobilise in difficult situations. The IPIP-BFM was used to measure the following personality traits: extraversion, agreeableness, conscientiousness, emotional stability and intellect. Polish (n = 66) and Slovak (n = 99) athletes participated in the study during the so-called second stage of the COVID-19 pandemic, from January 1 to February 12, 2021. Results: a) stress levels among Polish and Slovak athletes depend on their personal resources, which include resilience and the Big Five personality traits, b) Slovak athletes are characterised by greater perseverance, openness to experience and sense of humour, tolerance of negative emotions, treating life as a challenge, optimism and the ability to mobilise in difficult situations, c) higher resilience among Slovak athletes is a probable cause of the lack of difference in stress levels among Polish and Slovak athletes, d) female athletes from Poland and Slovakia reported higher emotional tension, external stress and intrapsychic stress during the second stage of the pandemic than did male athletes.